Development and Content Validity of an Instrument for Assessing the Fundamental Aspects of Academic Integrity - Lubis, Dhea Anisa Yuri; Aryanty, Nindya; Raudhoh, Siti; Kim, Jaegyun (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
Background: Academic integrity is a form of adherence to the principles that exist in academics. Several people have tried to develop instruments but none of the instruments explained the six fundamentals. The purpose of this study was to develop an instrument related to academic integrity by discussing six fundamental academic values as well as conducting content validity and readability tests. Method: The type of research used is research and development with additional information with FGD and Expert review and readibility test. Where the samples collected passed 30 medical students in 7th semester. The sampling technique uses purposive sampling method. Result: Through the results of the FGD, categories divided into 6, 18 sub categories. Furthermore, these results are 39 items. Aiken's V results showed by analysis on three experts, 4 items were found to be invalid. The readability test found that all items could be understood well. The last result got 34 items which 1 items are not eligible fo the instrument. Conclusion: From 34 items are the result with 1 items removed because not eligible and 4 is not valid by Aiken’s V. The readibility showed all instrument explained enough Keywords: Academic Integrity; Academic Misconduct ; Education;